Features of speech development of children of primary preschool age with visual impairment - Okuneva A. A. (Society and Science: Future Development, 2023)
the article reveals the results of an empirical study of the characteristics of speech activity in children of primary preschool age with visual impairment.
Keywords: связная речь; нарушение зрения; дети дошкольного возраста; речевая деятельность; preschool children; speech activity; coherent speech; речевая способность; формирование речи; visual impairment; компоненты речи; speech components; speech formation; speech ability